OVERVIEW OF THE APPLICATION OF ANIMAL WELFARE IN BALI CATTLE FARMS IN THE HIGHLANDS AND LOWLANDS IN GIANYAR REGENCY OF BALI - Widiantara, Gede; Kadek Karang Agustina,; I Made Sukada, (Buletin Veteriner Udayana, 2024)
Increased demand for beef requires optimisation of animal husbandry, which in turn leads to improved management of livestock production. This situation must be balanced with the application of animal welfare principles, where a prosperous livestock situation will support optimal production. Geographical differences are one of the factors that determine the knowledge of farmers and the implementation of animal husbandry management. This study aims to determine the description of the application of animal welfare in Balinese cattle farms in the highlands located in Puhu Village and and lowlands located in Pering Village, Gianyar Regency. An observational design was conducted, data collection was done by directly interviewing Balinese cattle owners with the guidance of a set of questionnaires. Data were tabulated and then analysed qualitatively and presented in tabular form. To differentiate the application of animal welfare in the two research locations, the Mann Whitney test was conducted. The application of animal welfare on Bali cattle farms in the highlands, was in the category of less than 5%, sufficient 50%, and good 45.0%; while in the lowlands, it was in the sufficient category with a percentage of 45.5%, and the good category 54.5%. No significant differences were found in the animal welfare principles in the two sample villages. Farmers are expected to further improve their knowledge and application of animal welfare principles to increase livestock productivity.